The perception of local communities towards hotel developments in Malaysia Islands / Nur Amalina Amira Ramli and Nurul Fatrah Aidah Zulkifli - Ramli, Nur Amalina Amira; Zulkifli, Nurul Fatrah Aidah (2017)
Hotel industry is one of the industries that are growth rapidly year by year around the world. It is interesting to know what is the people perception or thought about this industry, especially the perception of local communities. The developments of hotel industry surely give an impact toward the local communities at the place and it also will affect their perception towards that industry. As everyone knows perception is the thought that come after something happened or affected the individual life or surroundings. For hotel industry development, the thing that will be affected from the development is economic, environment and social. So this study is about to analyze and to know what is the local communities perception towards hotel industry development based on the impact of economic, environment and social.